High spatial resolution landscape indicators show promise in explaining water quality in urban streams - Ruan, Xiaofeng; Huang, Jieying; Williams, Dave A.R.; Harker, Karly J.; Gergel, Sarah E. (Ecological indicators, 2019)
•High resolution imagery are used to link landscape indicators with water quality.•Imagery at 5 m resolution was optimal for assessing impervious surfaces.•Dissolved oxygen and fecal coliform were well explained by indicators.•Configurational indicators at riparian zone level were important. Urban streams are subject to a myriad of complex stressors associated with impervious surfaces, which impact delivery of pollutants. Landscape indicators (e.g. the amount and arrangement of land cover) are widely used to help monitor water quality, yet their application in highly urbanized settings remains poorly understood. Here, we explored the utility of landscape indicators for explaining water chemistry and bacterial concentrations in streams throughout the Greater Vancouver Regional District, British Columbia, Canada. First, we compared high and moderate spatial resolution imagery to evaluate their relative efficacy in characterizing impervious surfaces. Second, we linked a suite of landscape indicators to major chemical properties and pollutants (e.g. dissolved oxygen, nitrate, turbidity, fecal coliform, E. Coli.) using a series of comparative statistical models. Land cover at 30-m resolution often over-estimated the proportional area of impervious surface by 0.10–0.30, sometimes doubling the amount detected using finer resolution imagery. Finer 5- and 2-m resolution imagery demonstrated little difference in estimating impervious cover. Therefore, 5-m resolution imagery was adopted for spatial analysis in the study region. Watershed-level landscape indicators explained nearly 50% of the variability in wet season concentrations of dissolved oxygen and fecal coliform. When considering the spatial configuration of impervious areas, edge density within the riparian zone explained more than 30% of the variability in fecal coliform and E. Coli. Our approach is potentially transferable to many cities worldwide facing similar challenges in monitoring urban streams.